ANALISIS PENERAPAN PRINSIP 5S BAGIAN PROSES PRODUKSI CRUDE PALM OIL PADA PT XYZ - Afriyanti, Elja; Maryam, Maryam (Politeknik ATI Padang, 2021)
The 5S concept (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) is a workplace management method aimed at improving efficiency, safety, and production quality through sorting, organizing, cleaning, standardizing, and instilling good work habits. This study was conducted at PT XYZ, a palm oil processing company, with the objective of evaluating the implementation of the 5S method. The study found that the company’s application of the 5S concept was still relatively low, particularly in the aspects of Seiri, Seiton, Seiso, and Seiketsu. Key challenges included material piles, lack of cleanliness in the production area, and minimal maintenance of machinery and equipment. To address these issues, various improvement proposals were made, such as regular workplace cleaning, better material organization, and employee training to enhance responsibility and work discipline. Following the implementation of these proposed improvements, the assessment score for the 5S method increased from 40% to 75.55%. The results of this study indicate that the proper implementation of the 5S method can improve production efficiency, product quality, and workplace safety, with positive impacts on the overall performance of the company.